Paediatric neuropsychological assessment: an analysis of parents' perspectives. Issue 1 (4th February 2014) - Stark, Daniel; Thomas, Sophie; Dawson, David; Talbot, Emily; Bennett, Emily; Starza-Smith, Arleta
Abstract : Purpose: – Modern healthcare services are commonly based on shared models of care, in which a strong emphasis is placed upon the views of those in receipt of services. The purpose of this paper is to examine the parents' experiences of their child's neuropsychological assessment. Design/methodology/approach: – This was a mixed-methodology study employing both quantitative and qualitative measures. Findings: – The questionnaire measure indicated a high overall level of satisfaction. Qualitative analysis of parental interviews provided a richer insight into the parental experience and indicated four major themes. Practical implications: – Implications covered three major areas. Firstly, whilst a high value was placed upon the assessment, the need for further comprehensive neurorehabilitation and intervention was highlighted. Secondly, this study highlights the significant adversity experienced by such families and subsequent unmet psychological needs which also require consideration. Finally, findings from the current study could assist in improving future measures of satisfaction in similar services. Originality/value: – This is the first published study of parental experiences of and satisfaction with paediatric neuropsychological assessment in the UK.